(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Introduzione - 2. Europa dei cittadini e identità politica del processo di integrazione continentale - 3. Spazio politico europeo, libertà religiosa e laicità - 4. Conclusioni. ABSTRACT: The evolution of the European Union law and of the right to religious freedom lies in the global process of internationalization of fundamental rights, the transformation of relations between States, the modification of the idea of sovereignty, the emergence of new conventional instruments. With reference to the European social and legal space, the transformation of the European Economic Community into a real political union has allowed the inalienable human rights of the people to become central in the process of integration. Because of that, the political and legal system of the European Union, characterized by the transition of the State monopoly of sovereignty to its sharing among different subjects, has affected the reality of relations between public powers and religious phenomenon. A particular configuration of the concept of secularism in the European continent has been established, by virtue, which the values of democracy, pluralism, human dignity and non-identification between public functions and religious experience would allow for peaceful coexistence between religion, institutional activity of the European Union and fundamental freedoms.